Nocebo/Placebo Effects in Dental Practice: Two Key Protagonists - Chavarría-Bolaños DDS, MSc., PhD, Daniel; Pozos-Guillén DDS, MSc, PhD, Amaury; Montero Aguilar MSc, Mauricio (Odovtos - International Journal of Dental Sciences, 2019)
Understanding the possible effects that a patient’s psycho-neurobiological processes (such as the nocebo effect) may have on the every-day dental treatments, could assist the clinicians in preventing the onset of adverse events not related directly with the clinical procedure. At the same time, employing pathways to trigger plausible placebo effects could aid the clinician to enhance the outcome of ordinary clinical procedures and the patient’s perspective. Identified factors, which could lead both to positive or negative effects, may be present in different ways. Prior personal experiences, second-hand information, alternative medicine, catastrophizing or patient motivation; all could have an indirect effect in the treatment outcome. A well-informed clinician should use such factors to individualize each patient treatment.